Investigate on welding distortion, residual stress and metallurgical behavior using fem and experimental study / Mohd Ridhwan Mohammed Redza - Mohammed Redza, Mohd Ridhwan (2016)
This study sets out to investigate the distortion, residual stress and metallurgical behavior o f low carbon steel due to single-pass and multipass GMAW process using finite element method (FEM). There are various cases studies were conducted started with the basic welding structure of butt joint which is divided into four (4) major case studies, which are (1) distortion analysis compared with analytical calculation FEM and experimental study on butt joint, (2) metallurgical behavior analysis on butt joint, (3) residual stress estimation analysis o f butt joint using analytical method.A welding simulation was created using FE commercial software package SYSWELD 2010 and Weld Planner 2010 with the capabilities to geometry welding processes. However, in the simulation study, the FEA commercial software was employed to predict welding distortion, residual stress and metallurgical behavior in butt joint weld o f low carbon steel with thicknesses of 4 mm, 6 mm and 9 mm. It was found out that, the 2D multipass analysis could be employed to obtain the fast average result o f angular distortion while 3D multipass analysis to produce more accurate and complete results. For verification purpose, a series o f experiments were performed to measure the weld. Therefore, the experimental works were conducted by using GMAW fully automated robotic welding process. By comparing the results, It can be summarized that the 3D analysis, simulation shows reasonable agreement and good correlation with experiments, except in 2D analysis on geometry. This result o f the study indicates that the simulation study is a reliable tool in predicting the welding induced on the particular geometry and welding joint in this study. The effects o f the clamping and welding sequence on distortion were also investigated in this study, and it was found out that the clamping condition and the welding sequences play a considerable factor in distortion, residual stress and metallurgical behavior.